2015
DOI: 10.1016/j.cell.2015.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Signaling Shapes Vestibulo-Motor Circuit Specificity

Abstract: The ability to continuously adjust posture and balance is necessary for reliable motor behavior. Vestibular and proprioceptive systems influence postural adjustments during movement by signaling functionally complementary sensory information. Using viral tracing and mouse genetics, we reveal two patterns of synaptic specificity between brainstem vestibular neurons and spinal motor neurons, established through distinct mechanisms. First, vestibular input targets preferentially extensor over flexor motor pools, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 50 publications
(85 reference statements)
7
65
0
Order By: Relevance
“…Collectively, vestibulospinal projections constituted 8% of supraspinal projections to the graft (Figures 3L and 3M). Vestibulospinal neurons make monosynaptic contacts onto premotor spinal interneurons (Bourane et al., 2015), and the lateral vestibular nucleus (LVe) innervates motor neurons at lumbar levels of the spinal cord (Basaldella et al., 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Collectively, vestibulospinal projections constituted 8% of supraspinal projections to the graft (Figures 3L and 3M). Vestibulospinal neurons make monosynaptic contacts onto premotor spinal interneurons (Bourane et al., 2015), and the lateral vestibular nucleus (LVe) innervates motor neurons at lumbar levels of the spinal cord (Basaldella et al., 2015). …”
Section: Resultsmentioning
confidence: 99%
“…W. Yang et al, 2009). SST cINs in the primary somatosensory cortex (S1) were targeted using AAV viral injections in mice carrying an SST Cre allele and a conditional compound synaptophysin1-eGFP (Syp-eGFP) construct, which functions as a presynaptic reporter (i.e SST cre ;R26R Figure1A) (Basaldella et al, 2015;Li et al, 2010;Wamsley et al, 2018). To modulate the activity of SST cINs, these mice were injected at P0 with Cre-dependent AAVs that drive the expression of either KIR2.1 or NaChBac channels along with an mCherry reporter ( Figure 1A, B).…”
Section: Neuronal Activity Affects the Synaptic Development Of Sst Cinsmentioning
confidence: 99%
“…Since this motor neuron subclass is recruited for postural tasks, the revealed specific connectivity matrix from brainstem vestibular neurons thus matches perfectly this behavioral requirement. We found that the precision of these synaptic connections is established during development and requires multisensory signaling from both vestibular and proprioceptive sources (Basaldella et al , ). A third example of a functionally dedicated pathway was described in a recent collaborative study, in which we identified specific neurons in the periaqueductal gray in the midbrain involved in the regulation of defensive behavior, signaling through the caudal brainstem nucleus Mc (Tovote et al , ).…”
Section: The Spinal Cord As a Highly Organized Final Executive Centermentioning
confidence: 99%
“… (A) Scheme displaying brainstem nuclei with neurons premotor to forelimb (FL) and hindlimb (HL)‐innervating spinal motor neurons in different colors (adapted from Esposito et al , ); especially highlighted are MdV, needed for efficient forelimb grasping, and the vestibular nucleus (Ve), with a role in posture and balance. (B) Connectivity between neurons in the vestibular nucleus and hindlimb‐innervating motor neurons (adapted from Basaldella et al , ). Note that Ve input is biased to extensor over flexor motor neurons (interpool specificity) and within the extensor pool to slow over fast motor neurons (intrapool specificity).…”
Section: The Spinal Cord As a Highly Organized Final Executive Centermentioning
confidence: 99%
See 1 more Smart Citation